Overhauling dental implications in a child with rare craniofrontonasal syndrome: a case report - Tyagi, Rishi; Khatri, Amit; Kalra, Namita; Khandelwal, Deepak; Garg, Neetu; Yangdol, Padma; Kulkarni, Shruti (International Journal of Contemporary Pediatrics, 2024)
Craniofrontonasal syndrome is an extremely rare X-linked dominant genetic disorder characterized by features such as hypertelorism, craniosynostosis, ocular anomalies, a bifid nasal tip, and longitudinal ridging with splitting of the nails. Heterozygous females are more severely affected, presenting frontonasal dysplasia and coronal craniosynostosis (fusion of the coronal sutures), while males typically only exhibit hypertelorism. This case report describes the dental management of a 9-year-old female with craniofrontonasal syndrome who was referred to the department of paediatric and preventive dentistry for pain in the lower right and left back tooth region. The patient exhibited a clinical spectrum including microcephaly, short neck, axillary pterygium, clinodactyly of the toes, longitudinal ridging with split nails, pectus excavatum, and underdeveloped female genitalia. Extraoral examination revealed hypertelorism, flat nasal bridge, low-set ears, strabismus, antimongoloid slant, and an indistinct philtrum. Intraoral examination showed a high palatal vault, crowding of the upper and lower arches during the mixed dentition period, multiple dental caries, and poor oral hygiene. An orthopantomogram confirmed delayed dental development. Dental treatment was carried out on a dental chair system using adequate behaviour management techniques with short appointments, keeping in mind the reduced cooperative ability of the child. The importance of this report stems from the limited dental literature available on the syndrome. Preventive measures along with home care instructions were emphasized to support professional care.